A novel immunosensing platform for serotonin detection in complex real samples based on graphene oxide and chitosan. (10th July 2019) - Adumitrăchioaie, Alina; Tertiș, Mihaela; Suciu, Maria; Graur, Florin; Cristea, Cecilia
Abstract: A novel, simple and versatile nanocomposite platform based on graphene-oxide/chitosan modified screen printed electrode was optimized and used for the development of an immunosensor for the sensitive and highly selective electrochemical detection of serotonin. Graphene oxide has been used for providing carboxylic groups which form covalent bonds with the terminal amine groups from the antibody units, thus ensuring the immobilization of the biocomponent at the electrode surface. The presence of chitosan is necessary to ensure the stability of the nanomaterial film deposited on the electrode' surface during the modification steps. The platform development protocol was optimized throughout the study by using electrochemical methods (electrochemical impedance spectroscopy, cyclic voltammetry and differential pulse voltammetry) as well as scanning electron microscopy. The following steps, namely immobilization of the antibody, blocking of the active free sites from graphene template with bovine serum albumin and testing of the immunosensor after immobilization of the analyte molecules at the surface, were optimized based on the differential pulse voltammetry tests following the signal obtained for the electrochemical oxidation of serotonin. The newly customized sensor was found to have a detection range from 10 nM to 100 μM and a limit of detection of 3.2 nM, being used for serotonin detection from human serum, saliva, artificial tears and urine samples as well as in the presence of different interferences, when good recovery rates were obtained. Graphical abstract: Image 1